CYBER INFRINGEMENTS: ANALYZING JUDICIAL AND LEGISLATIVE SAFEGUARDS FOR WOMEN'S PRIVACY RIGHTS IN INDIA - Sharma, Rupaksh; Shadangi, Susanta Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Privacy is one of the necessary requirements that cannot be arbitrarily implemented in any society. People in the same continent may understand privacy as an individual right to privacy in different ways. Appreciation of privacy at global level can be interpreted in Universal Declaration of Human Rights as a liberty right, which is an inherent part of the mankind. With that is evident that privacy violation is not limited to the physical spaces; rather, a person can be violated in all types of computer media. As dependency on internet grows and, therefore use of virtual modes, there are several considerations since people may not be prepared for new technologies I n performing everyday tasks. The matter becomes more complicated when privations are committed against the most helpless in the society. Women and sexual minorities take most of the heat of privacy violations since the society today is embedded in a patriarchal system. Women may face various other sub-violations on the internet which may be included under the title of Technology Facilitated gender-based violence (TFGV). Infringement of privacy is a violation of fundamental rights as recognized under the right to life and personal liberty but privacy violations that take place on digital platforms is not acknowledged and recognized yet. Women are vulnerable to a range of sub-violations, referred to as Technology Facilitated Gender-Based Violence while using the internet. Infringing on someone's privacy is a violation of their fundamental rights, such as the right to life and personal liberty. However, privacy violations that occur on digital platforms are yet to be fully recognized and acknowledged. It is imperative to address these issues to ensure that women are safe and secure while using digital platforms. In this paper, research examines the adequacy of current Indian legal frameworks in protecting women's privacy in digital spaces. Its purpose is to propose legal reforms that enhance the protection of women's digital privacy rights, taking into account global standards and best practices. The research objectives underscore the discrepancies between statutory provisions and their practical enforcement, offering a critical analysis of the existing legal framework and proposing enhancements to more effectively safeguard women against cybercrimes.